Migration, sustainable development and the role of business - C. B. Bhattacharya; Ursula Moffitt (UN Chronicle, 2013)
Over the past decades, business has begun reacting to growing societal pressures by broadening its focus from profit maximization alone to the “triple bottom line” of people, planet and profit.1 In the years since this concept was first introduced, people and planet focused sustainability initiatives have become standard practice amongst businesses across the world. Yet, migration is often overlooked as a factor within a company’s overall sustainability strategy. Such an oversight is critical, as migration invariably impacts business, and ensuring that its influence remains positive requires both awareness and engagement amongst corporate leadership. Migration can offer opportunities within each aspect of the triple bottom line, for instance, by creating a diverse and competent workforce, fostering innovation across borders and creating possibilities for globally integrated strategies in the realm of environmental sustainability.